2010
DOI: 10.1096/fj.09-152611
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping ofAHI1as a schizophrenia susceptibility gene: from association to evolutionary evidence

Abstract: In previous studies, we identified a locus for schizophrenia on 6q23.3 and proposed the Abelson helper integration site 1 (AHI1) as the candidate gene. AHI1 is expressed in the brain and plays a key role in neurodevelopment, is involved in Joubert syndrome, and has been recently associated with autism. The neurodevelopmental role of AHI1 fits with etiological hypotheses of schizophrenia. To definitively confirm our hypothesis, we searched for associations using a dense map of the region. Our strongest findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 127 publications
5
35
0
1
Order By: Relevance
“…Therefore, our study has identified a major role of MAP7 in the developmental regulation of collateral branch formation of DRG sensory axons. Because MAP7 has been associated recently with autism and schizophrenia (Torri et al, 2010;Venkatasubramanian, 2015;Rouillard et al, 2016), one can imagine that it influences branch morphogenesis of other neuronal cell types that are critical to these neurological disorders. Therefore, it would be interesting to further analyze MAP7 function in other parts of the nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our study has identified a major role of MAP7 in the developmental regulation of collateral branch formation of DRG sensory axons. Because MAP7 has been associated recently with autism and schizophrenia (Torri et al, 2010;Venkatasubramanian, 2015;Rouillard et al, 2016), one can imagine that it influences branch morphogenesis of other neuronal cell types that are critical to these neurological disorders. Therefore, it would be interesting to further analyze MAP7 function in other parts of the nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the only known MAP7 function is linked to spermatogenesis and histocompatibility (Komada et al, 2000;Magnan et al, 2009). Despite its expression in the nervous system (FabreJonca et al, 1998;Komada et al, 2000) and the recent finding of MAP7 association with autism and schizophrenia (Torri et al, 2010;Venkatasubramanian, 2015;Rouillard et al, 2016), the function of MAP7 in neurons has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is conceivable that variants affecting cognition are still evolving adaptively in anatomically modern humans [4,38], although no specific evidence for this has been reported to date. While several genes involved in neural development and cognitive performances have been identified as targets of natural selection in modern human populations [14,25,30,53,64], none of their polymorphisms has been reliably shown to influence intelligence, the only exception being a nonsynonymous SNP in BDNF [36]. Still, in this latter case the Met66 allele, which is thought to have been driven to high frequency by selection, has a negative impact on cognitive abilities [12].…”
Section: Introductionmentioning
confidence: 99%
“…Later studies revealed that nonsense or frame-shift mutations in AHI1 are associated with Joubert syndrome, a rare autosomal recessive disorder characterized by abnormal brain development and mental retardation (2,3). Recently, fine mapping (4,5), association (6), and replication (7,8) studies have identified AHI1 as a susceptibility gene for schizophrenia, a major neuropsychiatric disorder associated with depression. The AHI1 gene locus has also been linked with autism, which overlaps with a schizophrenia haplotype (9) and is also seen in some patients with Joubert syndrome (10).…”
mentioning
confidence: 99%